Teknik Simak Catat bagi Pemelajar BIPA dalam Kemampuan Menulis Kosakata: Studi Riset oleh Pemelajar Islamwittaya School - Adinda Ramadhani; Mutia Febriyana (Universitas Muhammadiyah Jember, 2025)
This study aims to improve the vocabulary writing ability of Indonesian for Foreign Speakers (BIPA) learners through the Simak-Catat technique in Matthayom 5 class at Islamwittaya School. The subject of the research is Matthayom 5 class at Islamwittaya School which consists of 22 learners. The method used was Classroom Action Research (PTK) conducted in two cycles, with each cycle including planning, action, observation, and reflection stages. Data were collected through vocabulary writing skill test, documentation, and direct observation. The results showed that the vocabulary writing ability of BIPA learners had improved significantly. In the pre-action stage, the class average score was 64 (poor category). In cycle I, after the application of the simak catat technique, the average score increased to 79 (fair category). Improvements in cycle II by paying attention to time allocation and using paper media with pictures of objects around the classroom resulted in an increase in the average score to 90 (good category). A significant increase can be seen from the percentage of learners who scored very well, from none in the preaction, increasing to 14% in cycle I, and reaching 45% in cycle II. The teacher activity observation also showed an increase from 79% in cycle I to 91% in cycle II, while the learner activity observation increased from 62% to 88%. This study concludes that the simak catatat technique is effective in improving the vocabulary writing ability of BIPA learners, by encouraging learners to actively record and process linguistic information systematically and contextually.